Diagnostic utility of endoscopic duodenal biopsies and histopathological finding in upper gastrointestinal diseases: A 2-year analysis - Amruta Ashok Patil,; Sagar More,; Arpana Shinde, (Asian Journal of Medical Sciences, 2022)
Background: Diseases of gastrointestinal (GI) tract present wit myriad signs and symptoms. Appropriate management of these diseases involves proper evaluation. Upper GI endoscopies are becoming increasingly popular because it helps in first localizing the lesion and then biopsy specimens can be obtained from affected area. Duodenal biopsy followed by histopathological examination may clinch the diagnosis in majority of the cases. Aims and Objectives: The aim of the study was to find out diagnostic utility of endoscopic duodenal biopsies and histopathological finding in the upper GI diseases. (1) To analyze duodenal endoscopic biopsy samples obtained from patients presenting with the upper GI symptoms. (2) To correlate endoscopic and histopathological findings in studied cases. Materials and Methods: A retrospective and prospective observational study was carried out at the private histopathology center over a period of 2 years. All the patients underwent upper GI endoscopy with duodenal biopsies using flexible endoscope. Histopathology of the samples obtained from endoscopic duodenal biopsies in patients presenting with the upper GI symptoms were analyzed. The endoscopic findings such as mass lesion or ulcerative lesion were correlated with histopathological findings. Results: Out of these 704 biopsies, 303 (43.04%) were esophageal biopsies, 220 [31.25%] were gastric, and 181 [25.71%] were duodenal biopsies. There were 129 (71.27%) males and 52 (28.73%) females with a M: F ratio of 2.5: 1. The mean age of the cases was found to be 54.7±12.32 years. Out of 181 biopsies which were performed in this study, 100 (55.25%) lesions were found to be having neoplastic etiology whereas 81 (44.75%) lesions were found to have non-neoplastic etiology. Among patients who were found to have duodenal growth on endoscopy well differentiated adenocarcinoma (15.47%) followed by moderately differentiated adenocarcinoma (6.63%) were the common pathologies. In cases of non-neoplastic etiology, non-specific duodenitis was most common pathology (17.13%). Conclusion: Endoscopic biopsy followed by histopathological examination is cornerstone of the management of patients presenting with intractable upper GI symptomatology.